2021
DOI: 10.3389/fncel.2021.668980
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Neuromodulation of Spike Timing Dependent Plasticity in Mature Adult Rodent and Human Cortical Neurons

Abstract: Synapses in the cerebral cortex constantly change and this dynamic property regulated by the action of neuromodulators such as dopamine (DA), is essential for reward learning and memory. DA modulates spike-timing-dependent plasticity (STDP), a cellular model of learning and memory, in juvenile rodent cortical neurons. However, it is unknown whether this neuromodulation also occurs at excitatory synapses of cortical neurons in mature adult mice or in humans. Cortical layer V pyramidal neurons were recorded with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Pharmacological modulation of D2 receptor activity did not affect plasticity directly, but only indirectly via inhibition of GABA release by interneurons (Chiu et al, 2010 ; Xu and Yao, 2010 ). In the presence of GABA, t-LTD or no change have been observed at almost all tested intervals (in both young adult and mature mice, Louth et al, 2021 ). Optogenetic activation of VTA DA fibers blocked t-LTD and this modulatory effect was abolished in the presence of the D2 receptor antagonist, but was not affected by the D1 receptor antagonist (Louth et al, 2021 ).…”
Section: Dopaminergic Modulation Of Long-term Synaptic Plasticity In ...mentioning
confidence: 95%
See 3 more Smart Citations
“…Pharmacological modulation of D2 receptor activity did not affect plasticity directly, but only indirectly via inhibition of GABA release by interneurons (Chiu et al, 2010 ; Xu and Yao, 2010 ). In the presence of GABA, t-LTD or no change have been observed at almost all tested intervals (in both young adult and mature mice, Louth et al, 2021 ). Optogenetic activation of VTA DA fibers blocked t-LTD and this modulatory effect was abolished in the presence of the D2 receptor antagonist, but was not affected by the D1 receptor antagonist (Louth et al, 2021 ).…”
Section: Dopaminergic Modulation Of Long-term Synaptic Plasticity In ...mentioning
confidence: 95%
“…In the presence of GABA, t-LTD or no change have been observed at almost all tested intervals (in both young adult and mature mice, Louth et al, 2021 ). Optogenetic activation of VTA DA fibers blocked t-LTD and this modulatory effect was abolished in the presence of the D2 receptor antagonist, but was not affected by the D1 receptor antagonist (Louth et al, 2021 ). The blockade of t-LTD by D2 receptors is consistent with the evidence of D2-mediated GABA suppression by DA acting by inhibiting its presynaptic release (Xu and Yao, 2010 ).…”
Section: Dopaminergic Modulation Of Long-term Synaptic Plasticity In ...mentioning
confidence: 95%
See 2 more Smart Citations
“…This may constitute an additional limitation to the transposition of the results observed in vitro . Several studies suggest that the capacity to induce t-LTD decreases with age (Banerjee et al, 2009 ; Verhoog et al, 2013 ) although a recent study has shown t-LTD at cortical layer V synapses in adult mice following pre-before-post protocol (Louth et al, 2021 ). Similarly, induction of t-LTD by a STDP protocol in the somato-sensory cortex of adult rats by pairing postsynaptic spikes and subthreshold whisker deflection is relatively frequent whereas induction of t-LTP in the same preparation is rare (Jacob et al, 2007 ).…”
Section: Reevaluation Of Stdp Rulesmentioning
confidence: 99%